O Estágio em um curso de pedagogia a distância: a visão dos alunos. - Lima, Marlene Haidem de Souza (2013)
This study had as purpose to research Supervised Internship, beginning from the observed dynamics of students in a distance learning pedagogy class, of a private university from São Paulo, and therefore it utilized reports and reflections of these students about the accomplished internship. This research leading question was to investigate ¿Which is the contribution of supervised internship for the students graduation in a distance learning pedagogy class?¿. As theoretical groundwork, this study utilized observations of Pimenta and Lima (2010), among others, considering that internship cannot be seen just as a bureaucratic fulfillment in the graduation path of a future professor. The research, which used a qualitative approach, focused case study, using the analysis of ten students reports sent to the Virtual Learning Environment (VLE) through the exercise of reflection about the internship, and, at a second moment, it took the data of an exploratory questionnaire answered by eleven students interns about the internshipfulfilled activities in a transferor school. Therefore, it is about employed instruments which objective is to know the students reflections sent to Virtual Learning Environment (VLE) and, also, in the classroom, in order to trace a parallel between the two internship moments, in other words, in the virtual environment and the classroom. The specific studies analyzed confirmed the positive sight of the internship students for the knowledge and encouragement of the teaching profession. There was emphasis on the responsiveness of professors and schools where occurred the internships, signaling an affective dimension of students relative to this phase of training of future teachers or professors. The question of the relationship between theory and practice did not find deepening by the trainees.